Radio and the Rise of the Nazis in Prewar Germany - Maja Adena; Ruben Enikolopov; Maria Petrova; Veronica Santarosa; Ekaterina Zhuravskaya (Center for Economic Studies and ifo Institute (CESifo), 2015)
How do the media affect public support for democratic institutions in a fragile democracy? What role do they play in a dictatorial regime? We study these questions in the context of Germany of the 1920s and 1930s. During the democratic period, when the Weimar government introduced pro-government political news, the growth of Nazi popularity slowed down in areas with access to radio. This effect was reversed during the campaign for the last competitive election as a result of the pro-Nazi radio broadcast following Hitler's appointment as German chancellor. During the consolidation of dictatorship, radio propaganda helped the Nazis to enroll new party members. After the Nazis established their rule, radio propaganda incited anti-Semitic acts and denunciations of Jews to authorities by ordinary Germans. The effect of anti-Semitic propaganda varied depending on the listeners' predispositions toward the message. Nazi radio was most effective in places where anti-Semitism was historically high and had a negative effect in places with historically low anti-Semitism.
Keywords: D72; L82; N74; 330; anti-semitism; dictatorship; media; Nazis; propaganda; unconsolidated democracy